2017
DOI: 10.1002/pat.4138
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a new class of poly(ether‐block‐amide)s via solvent free reactive processing

Abstract: Novel poly(ether-co-amide) block copolymers (PEA) with polyamide-6 as hard segments and different polyether (polyoxytetramethylene glycol [PTMG]/polyethylene glycol [PEG]) as soft segments were prepared via reactive processing. The chemical structure, crystalline properties, mechanical properties, water resistance, and thermal stability of as-prepared PEAs were extensively studied by Fourier transform infrared spectroscopy, X-ray diffraction, differential scanning calorimetry, dynamic mechanical analysis, tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Generally, low glass transition temperature ( T g ) oligomers such as poly(tetramethylene glycol) (PTMG), 14 poly(ethylene glycol) (PEG), 23 poly(propylene glycol), 24 polydimethylsiloxane (PDMS) 25 and polyester 26, 27 are employed as soft segments. As for the hard segments, most of them have strong polar groups, such as urethanes, ureas, imides and esters 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, low glass transition temperature ( T g ) oligomers such as poly(tetramethylene glycol) (PTMG), 14 poly(ethylene glycol) (PEG), 23 poly(propylene glycol), 24 polydimethylsiloxane (PDMS) 25 and polyester 26, 27 are employed as soft segments. As for the hard segments, most of them have strong polar groups, such as urethanes, ureas, imides and esters 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The soft segment, acting with high elasticity to TPAE, presents a random coil configuration [ 1 , 4 , 5 ]. The hard segments, acting as physical cross-linking points, are either glassy or crystalline at room temperature [ 6 , 7 ]. At present, aliphatic polyamides such as PA-6, PA-11 and PA-12 are selected as the hard segments for commercial TPAEs [ 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to this method, many kinds of TPAE have been successfully fabricated [ 5 , 10 ]. The advantage of this method is that the condition of reaction is mild [ 6 ]. However, the reaction is accompanied by the production of CO 2 , which is very difficult to remove with the high viscosity of the copolymer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies on aliphatic polyamide TPAEs have shown that the properties are not limited to changes in the molecular structure of the hard segment, 21,28,32,38,39 but also changes in the molecular weight of both the soft and hard segments. 1,29,40 Thus, in this study, PAPXD14/1214-PTMG elastomers were successfully prepared by controlling the molecular weight of the soft and semiaromatic polyamide hard segments. Meanwhile, the strategy of adjusting the benzene ring content in the semiaromatic polyamides was proposed to realize comprehensive improvement, as shown in Schemes 1 and 2.…”
Section: Introductionmentioning
confidence: 99%